CAUGHT IN THE BETWEEN: A COMPARATIVE READING OF THE EFFECTS OF TRADITION AND MODERNITY IN ANITA NAIR’S MISTRESS - JAYAN, KIRAN; CHITRA, DR. A. R. (SMART MOVES JOURNAL IJELLH, 2017)
The conventions and moral obligations that list down to rules for women in India are being tarnished with the spread of nuclear families. Women have started becoming partners in decision-making, thereby replacing the authoritative decisions from the head of the family (normally men). The novel Mistress written by Anita Nair portrays the conflicts of a woman who is independent with her mind and yet is forced to live in subjugation. The levels of subjugation entrusted in the bondage of marriage in India and the inescapable concept of ‘helpless’ women are considered in the paper. The paper also deals with the plight of the Indian woman who is caught between modern and traditional stereotypes